1980
DOI: 10.1002/bbpc.19800840612
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Electron Attachment to CCl4, CHCl3, CH2Cl2 and CH3Cl

Abstract: Apparate und Methoden / Elektronenaffinitat / Massenspektroskopie / Molekiilstruktur / Zwischenmolekulare WechselwirkungenResonance dissociative attachment of monoenergetic electrons in the energy range from 0.0 eV to 10 eV to CCl,, CHCI,, CH,CI, and CHJ1 has been studied using a trochoidal electron monochromator and a quadrupole mass filter. The following fragment negative ions as a function of electron impact energy could be observed: C1-. CI;, CCl; and CCI; from CCI,; CI-, HCI; and CCl; from CHCI,; CI-, Cl;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 23 publications
10
61
0
Order By: Relevance
“…However, if both C1 and F are constituents of the parent molecule, the energy integrated (up to 20 eV) intensity of F-after dissociative attachment always remains one or two orders of magnitude below that of C1- [18]. In the series of the chlorinated methanes the cross section for the production of C1-by dissociative attachment decreases drastically when C1 is replaced by H, in fact by three orders of magnitude from CC14 to CH3C1 [20]. Such a wide variation of the cross sections with the composition of the target molecule and such a stringent dependence on number and species of the halogen con-stituents of the respective halomethane has in fact not been observed for the production of negative fragments in ion-molecule collisions.…”
Section: A) Fragmentsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, if both C1 and F are constituents of the parent molecule, the energy integrated (up to 20 eV) intensity of F-after dissociative attachment always remains one or two orders of magnitude below that of C1- [18]. In the series of the chlorinated methanes the cross section for the production of C1-by dissociative attachment decreases drastically when C1 is replaced by H, in fact by three orders of magnitude from CC14 to CH3C1 [20]. Such a wide variation of the cross sections with the composition of the target molecule and such a stringent dependence on number and species of the halogen con-stituents of the respective halomethane has in fact not been observed for the production of negative fragments in ion-molecule collisions.…”
Section: A) Fragmentsmentioning
confidence: 94%
“…3d) with twice the number of fluorine atoms. In contrast to these rather small variances in the yield of negative fragments from the different halogenated methanes after ion impact, it is known from fluorinated methanes that the behaviour of these molecules with respect to electron attachment drastically changes when fluorine is replaced by chlorine [3,[17][18][19][20]. Here, it is generally observed that the production of F-starts to occur at energies considerably above the thermodynamic threshold while that Of C1-yields much higher peak cross sections near zero energy.…”
Section: A) Fragmentsmentioning
confidence: 99%
“…The energy resolution and performance at very low energies, as well as dynamic range, are superior to that in the apparatus used for absolute cross-section measurements, and we employ it to determine the energy dependences, that is, the shapes, of the DEA cross sections. Because the dominant negative ion fragment produced in these molecules is Cl Ϫ over the range of energies used here, 11,12 we need not be concerned with mass discrimination effects. Energy scale calibration to within Ϯ0.05 eV is carried out in this apparatus using a sharp peak in the negative ion production occurring very near zero energy.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…9 clearly shows the contribution from the upper resonance. As mass analyses show, 11,12 Cl Ϫ is the major stable anion fragment formed from both states. The present peak DEA cross section at 0.27 eV (9.63ϫ10 Ϫ16 cm 2 ) again supercedes that measured in an earlier crossed beam apparatus.…”
Section: B Dea In Selected Trichloroalkanesmentioning
confidence: 96%
“…The anions are, on the hand, scarce. CC14 molecule is one of the most extensively studied species of The CCl4-was for the first time as as this kind along with other halogen substituted methanes (1)(2)(3)(4)(5)(6)(7)(8) 1953 (26)(27)(28) and the adiabatic electron affinity (EA,,) of the and SF6. Much of the experimental data on electron attachment Parent CC14 molecule was first determined by magnetron techniis obtained from collision experiments with a beam of electrons ques (29)(30)(31) to be equal to2.06eV.…”
Section: Introductionmentioning
confidence: 99%